2017
DOI: 10.1186/s13068-017-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly, functional annotation, and analysis of the giant reed (Arundo donax L.) leaf transcriptome provide tools for the development of a biofuel feedstock

Abstract: Background Arundo donax has attracted renewed interest as a potential candidate energy crop for use in biomass-to-liquid fuel conversion processes and biorefineries. This is due to its high productivity, adaptability to marginal land conditions, and suitability for biofuel and biomaterial production. Despite its importance, the genomic resources currently available for supporting the improvement of this species are still limited.ResultsWe used RNA sequencing (RNA-Seq) to de novo assemble and characterize the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 83 publications
(102 reference statements)
4
32
0
Order By: Relevance
“…This is not a grapevine-specific problem: results of recent plant transcriptome annotation efforts indicated that our knowledge of gene function in higher plants is still limited. For example, a recent transcriptome analysis in rose-scented geranium ( Pelargonium graveolens ) and giant cane ( Arundo donax ) found protein homology to only 66% and 55% of the transcripts [ 48 , 49 ], respectively. Collectively, plant de novo transcriptome analysis studies confirmed that, despite the wealth of genomics and bioinformatics resources accumulated, our understanding of plant biology is still hindered by our inability to assign even tentative function to a large number of plant genes.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a grapevine-specific problem: results of recent plant transcriptome annotation efforts indicated that our knowledge of gene function in higher plants is still limited. For example, a recent transcriptome analysis in rose-scented geranium ( Pelargonium graveolens ) and giant cane ( Arundo donax ) found protein homology to only 66% and 55% of the transcripts [ 48 , 49 ], respectively. Collectively, plant de novo transcriptome analysis studies confirmed that, despite the wealth of genomics and bioinformatics resources accumulated, our understanding of plant biology is still hindered by our inability to assign even tentative function to a large number of plant genes.…”
Section: Discussionmentioning
confidence: 99%
“…Herbaceous 7-61 Mutant and clone collections; leaf and shoot transcriptomic sequences; studies on genetic diversity (AFLP, RAPD, and microsatellites markers) Khudamrongsawat et al, 2004;Zegada-Lizarazu et al, 2010;Pilu et al, 2014;Barrero et al, 2015;Canavan et al, 2017;Evangelistella et al, 2017;Malone et al, 2017;Valli et al, 2017 Reed canarygrass (Phalaris arundinacea L.) Pocienë et al, 2013;Lord, 2015 Virginia mallow (Sida hermaphrodita)…”
Section: Efficiency Of Light Interceptionmentioning
confidence: 99%
“…NAC and WRKY genes family are known to mediate water-(Hadiarto and Tran, 2011) and Na + -stress responses, as well as ABA signaling pathway in plants (Jiang et al ., 2017). Genes coding for stress-associated proteins (SAPs) are important regulators of multiple abiotic stress tolerance (Giri et al ., 2013) and found to be induced in water-stressed A. donax plants (Evangelistella et al ., 2017). However, only two SAPs were down-regulated in +Na and +NaP plants.…”
Section: Discussionmentioning
confidence: 99%
“…To this purpose, we used an integrated approach, combining physiological and biochemical measurements with transcriptomic analysis. Leaf and root transcriptomes of A. donax have been recently explored only in healthy plants (Sablok et al , 2014) and in plants exposed to drought stress (Fu et al , 2016; Evangelistella et al , 2017). Understanding, at molecular level, the response of A. donax to combined P and Na + stress is crucial for implementing adaptation strategies in order to achieve high biomass yield and productivity in marginal areas for agriculture.…”
Section: Introductionmentioning
confidence: 99%